Cervical Cancer and Human Papilloma Virus (HPV) Vaccines: A primer for General Physicians - Pooja Dwivedi; Anita Upadhyay Lahariya; Shalini Pandey; Aswathy Sreedevi; Ayush Lohiya; Chandrakant Lahariya (Preventive Medicine: Research & Reviews)
India contributes close to 20% of the global cervical cancer burden. This article reviews the preventive strategies against cervical cancer and suggest a few way forward for the prevention of cervical cancer in India. A literature review of online databases (Embase, Google Scholar, PubMed, Scopus) and reports from government websites regarding cervical cancer and HPV vaccination in India was conducted. Currently, four different HPV vaccines are available in India: a bivalent vaccine, a nonavalent vaccine and two quadrivalent vaccines. To reduce India’s cervical cancer burden, the National Technical Advisory Group on Immunization (NTAGI) has advocated the widespread implementation of HPV vaccination. An indigenous HPV vaccine was given market authorisation by the Drugs Controller General of India (DCGI) in July 2022. There is a need to raise awareness regarding the benefits of HPV vaccines in India. The introduction of indigenous HPV vaccine might enhance the supply logistics and may increase the uptake of the vaccine.